2022
DOI: 10.1038/s41598-022-18453-9
|View full text |Cite
|
Sign up to set email alerts
|

Elevated gamma-glutamyl transpeptidase level is associated with an increased risk of hip fracture in postmenopausal women

Abstract: The aim of this study was to evaluate the association between gamma-glutamyl transferase (GGT) levels and the risk of hip fracture among middle-aged women by using the Korean National Health Insurance Service claims database from 2002 to 2015. After exclusion of those with any chronic liver disease, heavy alcohol consumption, any missing values required for our analysis, or GGT levels less than 1 or greater than 99 percentile, we classified subjects into three groups according to baseline GGT levels. A total o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…GGT also exhibits sexspecific differences that showed a similar dynamic as AP in females. In line with these findings increased GGT levels have been suggested as an early marker for oxidative stress associated with pathological diseases beyond liver damage, including abnormal bone metabolism and a higher risk of hip fractures in women [35]. These elevations are not as pronounced as in liver diseases and therefore may still be within the reference interval but nevertheless can lead to a shift of the upper TML-RL.…”
Section: Flagmentioning
confidence: 66%
“…GGT also exhibits sexspecific differences that showed a similar dynamic as AP in females. In line with these findings increased GGT levels have been suggested as an early marker for oxidative stress associated with pathological diseases beyond liver damage, including abnormal bone metabolism and a higher risk of hip fractures in women [35]. These elevations are not as pronounced as in liver diseases and therefore may still be within the reference interval but nevertheless can lead to a shift of the upper TML-RL.…”
Section: Flagmentioning
confidence: 66%
“…(31) Large population-based cohort studies have also recently confirmed a significant association between GGT level and hip fracture risk. (32,33) However, there has been no previous study using GGT variability as a biomarker for risk assessment of osteoporotic fractures. The high variability of biomarkers has been attracting attention as a new factor predicting poor clinical outcomes of various diseases, and high GGT variability was identified as a predictor of increased risk of myocardial infarction, stroke, dementia, chronic kidney disease, and mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Large population-based cohort studies have also recently confirmed a significant association between GGT level and hip fracture risk [10,36]. However, there has been no previous study using GGT variability as a biomarker for risk assessment of osteoporotic fractures.…”
Section: Plos Onementioning
confidence: 96%